DESIGN AND IMPLEMENTATION OF A WEB-BASED LIBRARY INFORMATION SYSTEM USING PHP AND MYSQL FOR DIGITAL TRANSFORMATION IN CISARUA VILLAGE PUBLIC LIBRARY, SUKABUMI - RAJAGUKGUK, SOFIA; ADI DARMA, WAWANG; ERNAWATI, TIA; Badri Tamam, Moh (LPPM AMIK CBI Sukabumi, 2025)
This research aims to design and develop a Web-Based Library Information System in Cisarua Sub-District, Sukabumi City. Currently, the library still employs a manual system for borrowing, returning, and recording visit data, which results in inefficiencies and difficulties in data management. This information system is developed using PHP and MySQL technologies, and applies the Waterfall development method to ensure a structured process. The system design adopts the Model-View-Controller (MVC) approach and utilizes UML diagrams (Use Case, Activity, Sequence, Class) to visualize workflows and interactions among components. Additionally, ERD diagrams and database normalization up to the third normal form (3NF) are used to maintain data integrity and storage efficiency, which are crucial for accurate information management. The implementation results indicate that this system can replace manual processes with a digital system, enhancing library administrative efficiency, providing automated and real-time reporting, and facilitating data access and search. Functional testing through the black-box method yielded positive results from library administrators, indicating that the system satisfactorily meets user needs. However, there are some limitations, such as the absence of overdue return notifications and an application. This research is expected to contribute significantly to improving library service quality and serve as a reference for the.